The Determinants of Dividend Policy: A Study of Financial Industry in Indonesia - Gusni Gusni (Jurnal Keuangan dan Perbankan, 2017)
Dividend policy is still a controversial issue and often debated in the literature of corporate finance. Previous literature has examined that companies pay a dividend is to attract investors to buy their companies shares. The question, what are the determinants of the company’s dividend policy? The purpose of this study is to find out the determinants of dividend policy in the financial industry listed in Indonesia Stock Exchange. This study uses a panel data analysis method to investigate the determinants of dividend policy (corporate governance mechanism, profitability, systematic risk, firm size, and leverage) in Indonesia Stock Exchange which sample was taken from 17 companies by using purposive sampling technique from the period of 2009-2015. The empirical result shows that profitability, leverage, and institutional ownership have a negative impact on the firm’s dividend policy. This study revealed that systematic risk, firm size, and board of directors have no impact on the firm’s dividend policy.DOI: https://doi.org/10.26905/jkdp.v21i4.1521